Technique of the Analysis and Assessment of Innovative Industrial Risks at Different Stages of Innovative Activity - Gilyazutdinova, Irina Vladimirovna; Ponikarova, Anna Sergeyevna; Romanova, Anna Ilinichna; Rakhmatullin, Ashat Irekovich; Tukhvatullin, Rafael Fazulovich; Elokhova, Tatiana Aleksandrovna (International Journal of Economics and Financial Issues, 2016)
High rates of innovation in enterprises require setting a number of scientific and technical problems related to the evaluation and analysis of innovative industrial risks and their control systems. The article proposes an original technique for evaluation of innovative industrial risks at different stages of innovation. Its feature is that the rate determined by the survivability of the economic system. The basis of the study developed the method for determining the survivability is the definition of the integral index of vitality based on a comprehensive assessment of the production system. The closer the result of this indicator to one, the better the control system will determine the problem areas in the implementation of innovation and more efficient use of a set of measures to address the problems identified. Methods of assessing and analyzing the vitality of enterprises are available for the purposes of risk management as a tool of analysis to identify reasons for the decline performance of innovation. In this regard, we determined preliminary values of specific factors and the limit values for these indicators. Keywords: innovations, innovative industrial risks, stages of innovative activity, survivability of innovative economic systems JEL Classifications: E22, G32, G31